1863 : Lincoln's Pivotal Year - Gabbard, Sara Vaughn; Holzer, Harold (Book collections on Project MUSE., 2013)
"Only hours into the new year of 1863, Abraham Lincoln performed perhaps his most famous action as president by signing the Emancipation Proclamation ... Several defining moments of Lincoln's presidency took place in 1863, including the most titanic battle ever to shake the American continent, which soon inspired the most famous presidential speech in American history. The ten essays in this book explore the year's important events and developments, including the response to the signing of the Emancipation Proclamation; the battles of Gettysburg and Vicksburg, and other less-well-known confrontations; the New York City draft riots; several constitutional issues involving the war powers of President Lincoln; and the Gettysburg Address and its continued impact on American thought. Other topics include the adaptation of photography for war coverage; the critical use of images; the military role of the navy; and Lincoln's family life during this fiery trial."--Provided by publisher.